Religious Associations: Hosanna-Tabor and the Instrumental Value of Religious Groups - Ashutosh Bhagwat (Washington University Law Review, 2014)
In its 2012 decision in Hosanna-Tabor Evangelical Lutheran Church and School v. EEOC, the Supreme Court held that the Religion Clauses of the First Amendment require recognition of a “ministerial exception” to general antidiscrimination statutes (in that case, the ADA), because religious institutions must have autonomy in selecting their ministers. In the course of its analysis, however, the Court made a very interesting move. In response to the government’s argument that the case could be resolved under the general First Amendment right of association, the Court responded that this position was “untenable,” and indeed “remarkable,” because the very existence of the Religion Clauses indicated that religious groups must be treated differently from secular groups. It also rejected the view that its groundbreaking decision in Employment Division v. Smith, which interpreted the Free Exercise Clause extremely narrowly, precluded reliance on the Religion Clauses here, curtly distinguishing Smith on the grounds that it did not involve “government interference with an internal church decision that affects the faith and mission of the church itself.” Hosanna-Tabor thus appears to stand for the propositions that religious groups are different from secular groups for constitutional purposes and entitled to extra constitutional protections, and further, that religious institutions such as churches possess broader Free Exercise rights than do individuals. In this Article, I argue that both these propositions are indefensible in light of the text, history, and purposes of the Religion Clauses. I further argue that granting religious institutions special constitutional rights raises some very difficult, ultimately irresolvable boundary problems regarding the scope of the ministerial exception.
Keywords: Hosanna-Tabor Evangelical Lutheran Church; School v. EEOC; Employment Division v. Smith; freedom of religion; First Amendment; constitution; Free Exercise